Monaural and binaural detection thresholds of amplitude modulation - Kordus, M.; Sęk, A. (Archives of Acoustics, 2004)
This study is concerned with the amplitude modulation (AM) detection thresholds for monaural and binaural listening. In the first experiment, using a Two-Alternative Forced-Choice (2AFC) method with an adaptive procedure 2-up 1-down, the monaural and binaural AM detection thresholds were measured. Sinusoidal carrier at a frequency of 160, 500, 1000 or 4000 Hz was amplitude-modulated by a single sinusoidal modulator at a frequency of 4, 32, 64 or 128 Hz. Due to a significant intersubject scatter of the results it was impossible to estimate the difference between the thresholds determined for monaural and binaural presentation of the stimuli. Therefore, in the next experiment, psychometric functions for AM detection for both monaural and binaural listening were determined. This experiment was carried out for sinusoidal carriers at frequencies of 5000, 2000 and 6000 Hz and for sinusoidal modulator at frequencies of 4, 64 and 128 Hz. The results of this experiment showed a statistically significant difference between slopes of the psychometric function (after the percent of correct responses was converted to the detectability, d’, domain) for monaural and binaural stimuli presentation. Assuming that the AM threshold coincided with d’ = 1 it can be stated that monaural and binaural AM thresholds are significantly different.